x+17+x+19-x=602

Simple and best practice solution for x+17+x+19-x=602 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+17+x+19-x=602 equation:


Simplifying
x + 17 + x + 19 + -1x = 602

Reorder the terms:
17 + 19 + x + x + -1x = 602

Combine like terms: 17 + 19 = 36
36 + x + x + -1x = 602

Combine like terms: x + x = 2x
36 + 2x + -1x = 602

Combine like terms: 2x + -1x = 1x
36 + 1x = 602

Solving
36 + 1x = 602

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + 1x = 602 + -36

Combine like terms: 36 + -36 = 0
0 + 1x = 602 + -36
1x = 602 + -36

Combine like terms: 602 + -36 = 566
1x = 566

Divide each side by '1'.
x = 566

Simplifying
x = 566

See similar equations:

| 15x-9x+5=20 | | 5.4-3.7-4.6=0.2-3.1 | | 3(y-4)+6(y+1)=57 | | (m+340)8=4256 | | 2x=15x^2 | | -4r-2(3r-8)=3r+1 | | 6x+48=8x-48 | | 17v/2=34/3 | | 12a^2-128a+256=0 | | 15.2=m-10.9 | | 5x-10(3x-6)=3(24-9x) | | -2(5y-1)+4y=4 | | 4x+7=3+2x | | -15.2=m-10.9 | | -15-2=m-10.9 | | ln(3x+4)=2.6 | | -5(2x+1)3x=37 | | 5x-11=x+21 | | n^2-7n-60= | | -25X^2+300=0 | | Ln(3x+4)=3.6 | | -8x-2=15 | | p+p+20+p*3-34=526 | | 18.50+1.00x=30.6 | | 36=2(4y+2) | | 5x-15y=-75 | | 26-x=x-24 | | 2X^2+2X+15=0 | | 18.50+1.00x=26.5 | | 40=68-20log(t+1) | | (x-7)+7=(x+7)-7 | | 18-7y=-18 |

Equations solver categories